Time to go beyond RWA variability for IRB banks: An empirical analysis - Francesco Cannata; Simone Casellina; Gaetano Chionsini (European Banking Authority (EBA), 2020)
Fifteen years after the introduction of the Basel II Accord, which thoroughly revised the capital framework for banks, internal models are a full part of the supervisory toolkit and the risk management framework of financial institutions. The debate around models has gone through different phases: strong support right before Basel II, seeking greater risk-sensitivity of capital requirements; material concern after the financial crisis, in the light of the high variability of internal models' outcomes; and awareness at the current juncture of their important role in risk management and banking supervision. Despite all initiatives taken by banking regulators and supervisors, a number of questions on banks' risk-weighted assets are still open. The aim of this paper is to provide a different perspective on some of those questions and set the conditions for shifting the attention from simple comparison across banks to an economic interpretation of their risk measures.
Keywords: 330; Bank capital; prudential regulation; risk weights; Basel II